Addressing Unfunded Training Mandates in Hospitals : Engaging the Private Sector in Low- and Middle-Income Countries - Preker, A. S. (2012)
Health worker finance and provision are discussed in this article in the context of the global shortage of human resources. Key issues related to public and private finance or provision of tertiary health education institutions are highlighted, and costs, benefits, and feasibility of potential financing or provision solutions are identified. Engagement of the private sector can expand the resources available for education and align incentives to address an important inefficiency: the unfunded mandate of post-graduate in-service training at hospitals that jointly provide education and health services.